Students' Mathematical Problem-Solving Ability on Social Arithmetic Material - Indra Dwi Nugraha (Papanda Publisher, 2022)
This study aims to describe the ability of elementary school students in solving mathematical problems on social arithmetic material. This study uses a descriptive method with a qualitative approach about how students' mathematical problem solving abilities correlate with how students reduce and present data. In this study, the research subjects were six grade VI students, which were grouped into students with high, medium and low ability categories. The instruments used in collecting data are questions and interviews. The data collected were analyzed using four stages of mathematical problem solving skills, namely understanding the problem, formulating a problem plan, solving problems, and reviewing. The results showed that 16.67% of students had high mathematical problem solving abilities, 50% of students had moderate or intermediate abilities in solving mathematical problems and 33.33% had low mathematical problem solving abilities. Based on the results of the study, it can be concluded that grade VI elementary school students in Karawang Regency have moderate mathematical problem solving abilities in solving social arithmetic problems.